The prevalence of melanocytic naevi among schoolchildren in South-Hungary - Csoma Zsanett (JOURNAL OF THE EUROPEAN ACADEMY OF DERMATOLOGY AND VENEREOLOGY, 2008)
Malignant melanoma is an increasing public health problem worldwide; accordingly, identification of the constitutional and environmental factors which contribute to the development of the disease, and hence identification of the individuals at high risk of melanoma, is an indispensable step in all primary prevention efforts. This paper aims to assess the prevalence of different pigmented lesions among schoolchildren and to investigate their relationship with phenotypic pigmentary characteristics, sun exposure and other factors. A cross-sectional study was performed in two secondary schools in Szeged, Hungary. A total of 1320 schoolchildren, aged 14 to 18 years, underwent a whole-body skin examination. A standardized questionnaire was used to collect data on phenotypic, sun exposure and other variables. One to 10 common melanocytic naevi were found in 27% of the participants, and the naevus numbers were in the range of 10-100 in 67%; 5.4% of them had more than 100 common melanocytic naevi. The prevalence of clinically atypical naevi was 24.3%. Statistically significant associations were found between the number of pigmented lesions and gender, hair colour, eye colour, skin phototype, a history of severe painful sunburns and a family history of a large number of melanocytic naevi. Our study population displayed a markedly high prevalence of clinically atypical melanocytic naevi. Moreover, a considerable proportion of the investigated individuals had multiple common melanocytic naevi. Since the presence of a large number of melanocytic naevi is a strong predictor for future melanoma development, health educational programmes on melanoma prevention should be aimed at young age groups.